#### Answer

2(x-2) ($x^{2}$+2x+4)

#### Work Step by Step

2$x^{3}$-16=2($x^{3}$-8)=2($x^{3}$-$2^{3}$)=2(x-2)($x^{2}$+2x+$2^{2}$)=2(x-2) ($x^{2}$+2x+4)

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

2(x-2) ($x^{2}$+2x+4)

2$x^{3}$-16=2($x^{3}$-8)=2($x^{3}$-$2^{3}$)=2(x-2)($x^{2}$+2x+$2^{2}$)=2(x-2) ($x^{2}$+2x+4)

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.